Antifungal and eliciting properties of chitosan against Ceratocystis fimbriata in sweet potato. (1st December 2018) - Xing, Ke; Li, Teng Jie; Liu, Yuan Fang; Zhang, Jian; Zhang, Yu; Shen, Xiao Qiang; Li, Xiao Yan; Miao, Xiang Min; Feng, Zhao Zhong; Peng, Xue; Li, Zong Yun; Qin, Sheng
Highlights: Chitosan inhibited the cell growth and led to the cell necrosis of C. fimbriata . Chitosan altered the chitin deposition and fatty acid composition of C. fimbriata . Chitosan effectively controlled the C. fimbriata development in sweet potato TRs. The PAL and SOD activity were enhanced, while the MDA production was decreased. Chitosan exhibited the dual effects to control C. fimbriata in sweet potato. Abstract: The inhibitive effects of chitosan on black rot disease caused by Ceratocystis fimbriata in sweet potato tuber root (TR) were evaluated. The results demonstrated that chitosan effectively inhibited the mycelial growth and spore germination of C. fimbriata and directly led to the cell necrosis. Chitosan altered the chitin deposition and influenced the fatty acid composition of C. fimbriata . The application of chitosan effectively controlled the C. fimbriata development in sweet potato TRs 17 days of storage 25 °C. Phenylalanine ammonia lyase (PAL) and superoxide dismutase (SOD) activity were clearly enhanced by the chitosan treatment, while the malondialdehyde (MDA) production was not increased. These findings suggest that chitosan effectively controlled the infection of C. fimbriata in sweet potato TRs owing to its antifungal and eliciting properties, which induced some defense responses during storage.